Cyber PPAT and Legal Certainty in Indonesiaâ€™s Electronic Land Certification System - Muhayar, Muhayar; Deni, Fitra; Barus, Zulfadli (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
The digitalization of land registration in Indonesia, particularly through electronic land certificates, reflects a major reform in legal and administrative governance. This study examines the evolving role of the Land Deed Official (PPAT) in ensuring legal certainty amid the transition from conventional to electronic land certification. Employing a normative-empirical legal approach and case study in Bekasi Regency, the research explores how PPAT adapts to digital platforms while maintaining legal compliance. Findings reveal that electronic certification enhances efficiency, transparency, and security. However, its implementation faces significant challenges, including fragmented data systems, inadequate infrastructure, limited digital literacy, and the absence of specific legal norms regulating PPATâ€™s digital responsibilities. To address this gap, the study introduces the concept of â€œCyber PPATâ€â€”a redefined legal actor equipped with both legal and digital competencies. This study contributes to the discourse on land administration reform by underscoring the need for harmonized regulations, improved infrastructure, and institutional readiness. It emphasizes that legal certainty in digital land governance depends not only on technology but on the strength of the legal framework and institutional trust supporting it.